Fantastika in Calvinova postmodernistična pripovedna dela - Štoka, Tea (Primerjalna književnost, 2005)
The Fantastic and Postmodern Fiction of Calvino. The discussion deals with the dimension of the fantastic in the literary fiction of Italo Calvino (1923-1985). The most notable fantastic elements figure in Calvino's mature phase and, in the opinion of a consensus of critics, belong to his so-called postmodern period, which lasted from 1965 to 1980. The fantastic presupposes a natural experience of reality in which the supernatural is also present. This type of postmodern writing necessarily implies a dual reading of reality.
Keywords: Calvino, Italo, 1923-1985; italijanska književnost; postmodernizem; fantastika; fantastična književnost